Influence of wet-dry and freeze-thaw cycles on the physical and mechanical properties of MICP treated slope soil - Gowthaman, S.; Nakashima, K.; Nakamura, H.; Kawasaki, S. (American Rock Mechanics Association (ARMA), 2020)
Microbial induced carbonate precipitation (MICP) is a bio-mediated soil stabilization method, newly introduced in the field of Geotechnical engineering. Recent investigations have demonstrated that this technique, with several merits, has a significant potential for stabilizing the slope surface. As the MICP treated surfaces are exposed to various weathers including rainfalls, draughts and snowfalls, the durability investigations are requisite prior to the field-scale. The objective of this study is to evaluate the degradation of physical and mechanical properties of the MICP treated slope soil under cyclic wet-dry and freeze-thaw actions. Laboratory experiments were carried out in accordance with the standards. During the tests, mass loss, S-wave velocities and UCS of the specimens were determined. Based on the strength deterioration ratio (SDR), it is demonstrated that the freeze-thaw cycles degrade the physical and mechanical properties more significantly compared to that wet-dry cycles do. Propagation of uneven stresses during the increase in volume of porewater (while freezing) could develop microfractures and ruptures, weakening the properties of treated soil. It is also found that the carbonate content plays more important role in resistance to freeze-thaw more than that of wet-dry cycles. The results would be beneficial at design phase of the treatment, particularly for the considerations on effective life span.
Keywords: Durability; Wet- dry; Freeze - thaw; Slope soil stabilization; Microbial induced carbonate precipitation (MICP); Strength deterioration ratio (SDR)